Low-frequency bandgap broadening of single-phase shuriken-like acoustic metastructure through coupling design for sound insulation - Guo, Dongxu; Zhang, Xiaolong; Tian, Ruilan; Chen, Luqi (Applied acoustics, 2025)
[Display omitted] •A single-phase acoustic metamaterial (SSAM) can achieve low-frequency sound insulation.•Gradient and hybrid metastructures realize the ultra-wide sound insulation frequency range.•The local resonance mechanism of SSAM is proposed to study bandgap broadening.•The transmission, insertion loss, and experiment have verified sound insulation performance. Sound insulation has long been a prosperous subject with practical interest because it can reduce severe noise from moving vehicles. In this study, a single-phase shuriken-like acoustic metamaterial (SSAM) is proposed to broaden the low-frequency bandgap through gradient coupling design. Based on Bloch's theorem and finite element simulation method, the dispersion relation and transmission are studied, and the influence of structural geometric parameters on bandgap is investigated. The widest bandgap can reach 197.55 Hz, and the lowest frequency can be reduced to 54.96 Hz. Several combinations of metastructures with low-frequency continuous bandgap are constructed by gradient and hybrid coupling design for the SSAM structures. The calculated transmission in the frequency range of 1 to 10000 Hz showed an excellent increase in effective and perfect attenuation width. The influence of geometric configuration and parameters on the trend of the bandgap is qualitatively analyzed by combining the local resonance mechanism and an effective mass-spring system. The insertion loss (IL) of SSAM is obtained through numerical simulation, which is verified by the experiment. The experimental results show that the SSAM exhibits a high-pitched IL value of 24.9 dB at 870 Hz. These results indicate that the proposed SSAM configuration with distributed masses and periodical arrangement can realize a good broadband sound transmission loss (TL) by decreasing the opening frequencies of bandgaps. The proposed strategy of single-phase structural coupling designs facilitates the use of large-scale low-frequency noise canceling efficiently, promoting its potential engineering application. This work provides a new and effective method for generating wide bandgaps of honeycomb structures in complex low-frequency noise environments.